An Impact of Green Marketing on Practices of Supply Chain Management in Asia: Emerging Economic Opportunities and Challenges - Rath, Ramesh Chandra (International Journal of Supply Chain Management, 2013)
As the impact of “Green Marketing on the Practices of Supply Chain Management in Asia (GMOPOSCMA)” as concerned, it have been drawing the attention of both the academics and practitioners in the recent decades. However , no holistic frame work has been developed on how to build green industrial brands & industrial corporate brands. Whether or not sustainable, here, the green marketing and the green supply chain can be integrated with green industrial marketing in building greener organizations & industrial brands is still unclear. That’s why the supply chain management takes the leadership role in order to lead industrial marketing in to a great par in the world economic. In addition to that, little is known on the factors on green new industrial products are adopted by organization. Furthermore, we know little of whether and how- green marketing and its practices enables green new industrial product’s economic development. The special issue aims at the reflecting the most recent advances, on green industrial marketing, given sustainable supply chains & their interplay in given industrial branding & to explore future research directions. Therefore, the guest author of this copy right hopes that the solicited paper can provides insights on the impact of sustainable green marketing through the supply chains, in order to accelerates the theory of marketing from industry to industry and market to market through the practice of Green marketing on practices of Supply Chain Management.